2004
DOI: 10.5713/ajas.2004.491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Olive Cake in Complete Diet on Performance and Nutrient Utilization of Lambs

Abstract: Forty-five Najdi ram lambs were equally and randomly allotted to five dietary groups with three replications per diet to evaluate the effect of feeding olive cake in complete diet on nutrient digestibility, growth performance and carcass characteristics. The diets were: a whole-mixed control diet (C) containing 12% wheat straw and four diets; namely O, ON, OU and OUE, where crude olive cake, 3% NaOH-treated olive cake, 5% urea-treated olive cake (U) and ensiled U, respectively were incorporated to replace the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 9 publications
9
20
2
Order By: Relevance
“…The results obtained for CY were similar to those reported by Owaimer et al (2004), who did not find any effect from the inclusion of olive cake on CY at an inclusion level of 12%. In regard to the other carcass traits, Mioč et al (2007) found that lambs receiving the highest olive cake diet (30%) presented lower HCW and carcass yield than those fed the control diet or a diet with 15% of olive cake.…”
Section: Main Carcass Traitssupporting
confidence: 89%
See 4 more Smart Citations
“…The results obtained for CY were similar to those reported by Owaimer et al (2004), who did not find any effect from the inclusion of olive cake on CY at an inclusion level of 12%. In regard to the other carcass traits, Mioč et al (2007) found that lambs receiving the highest olive cake diet (30%) presented lower HCW and carcass yield than those fed the control diet or a diet with 15% of olive cake.…”
Section: Main Carcass Traitssupporting
confidence: 89%
“…Conversely, Owaimer et al (2004) did not find any differences in the muscle/bone ratio of the entire carcass of lambs fed rations containing 12% of olive cake.…”
Section: Ratios Among the Tissue Componentsmentioning
confidence: 60%
See 3 more Smart Citations